Occupant feedback on indoor environmental quality in refurbished historic buildings - Kamaruzzaman, S.N.; Zawawi, M.A.E.; Pitt, M.; Don, Z.M. (Academic Journals, 2010)
Since the year 2005, Malaysia has been moving away from constructing new buildings in favour of refurbishing historic and old ones. This is due to a number of reasons, including the economic crisis, land limitation and sustainable issues. However, when a historic building is refurbished, there is seldom any methodical study made of the occupants' opinions concerning indoor environmental quality. There are few studies on refurbished buildings on indoor environmental quality (IEQ) which should serve as a key building performance indicator. This study uses a questionnaire to document the occupant's perception towards the indoor environmental condition of six refurbished historic buildings in Malaysia. Analysis was carried out by normalising the data producing a fingerprint for preference as well as the level of importance. A correlation between preferences of the individual occupant score towards the overall buildng condition was also conducted. The paper shows that the questionnaire can be used effectively to survey all of indoor environment aspects as it has the advantage of looking at both negative and positive aspects of the environment. It is believed that this study would assist in the identification of any particular aspect of the environment that requires adjustment and improvement to provide a better internal environment for the occupants.